Expression of Tight Junction and Drug Efflux Transporter Proteins in an in vitro Model of Human Blood–Brain Barrier - Cioni, Chiara; Turlizzi, Elisa; Zanelli, Ugo; Oliveri, Giuseppe; Annunziata, Pasquale (Frontiers in Psychiatry, 2012)
Interendothelial cell tight junctions (TJs) proteins contribute to maintain the structural and functional integrity of the blood-brain barrier (BBB) and several efflux transporters regulate transport of compounds across BBB. A unique double compartment-model of the BBB, consisting of cerebral endothelial cells isolated from cryopreserved human glial tumors, alone and in the presence of human astroglial cells derived from the same tissue preparation was established. Endothelial cell viability and transendothelial electrical resistance (TEER) were measured in this model and three representative TJ proteins - occludin (OCLN), zonula occludens-1 (ZO-1) and claudin-5 (CLN-5) - as well as several drug efflux transporters - P-glycoprotein (P-gp), multidrug resistance protein-1 and 2 (MRP-1 and MRP-2), organic anion-transporting polypeptide-1 and 3 (oatp1 and oatp3) were analysed at both the protein and gene transcript level. Endothelial cell viability as well as TEER significantly increased in the presence of glial cells. A significant increase of expression of OCLN, ZO-1 and CLN-5 proteins as well as of several drug transporter proteins except oatp3 and MRP-1, was also found in the presence of glial cells. All the gene transcripts protein analysed were found to be significantly increased in the presence of glial cells. These results demonstrate that this brain endothelium culture system mimics a physiologically relevant situation and may therefore provide a new tool for studying the effects of biological fluids such as serum and cerebrospinal fluid from patients with neurological disorders underlying a BBB alteration in disease pathogenesis.